2004
DOI: 10.1073/pnas.0407066101
|View full text |Cite
|
Sign up to set email alerts
|

Evolving protein functional diversity in new genes of Drosophila

Abstract: The mechanism by which protein functional diversity expands is an important evolutionary issue. Studies of recently evolved chimeric genes permit direct investigation of the origin of new protein functions before they become obscured by subsequent evolution. Found in several African Drosophila species, jingwei (jgw), a recently evolved gene with a domain derived from the still extant short-chain alcohol dehydrogenase (ADH) through retroposition, provides an opportunity to examine this previously undescribed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
82
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 34 publications
4
82
0
1
Order By: Relevance
“…In this study we show the first case of protogenes identified in eukaryotic cytoplasmic genomes, and suggest that the generation of protogenes, as well as SSS, had served as a buffer, thus could also be a critical step for the establishment of CMS genes in natural populations. Our results also suggest that the previously recognized general features of new nuclear gene origination, including (1) recombination of existing genes and/ or previously non-coding sequences, leading to a hybrid gene structure, (2) sequence evolution driven by natural selection, and (3) acquisition of new functions [32,38,39], may also hold true for new mitochondrial gene formation. However, the microevolutionary process of the new mitochondrial genes we demonstrate here are much complicated than that of new nuclear genes reported so far.…”
Section: Discussionmentioning
confidence: 53%
“…In this study we show the first case of protogenes identified in eukaryotic cytoplasmic genomes, and suggest that the generation of protogenes, as well as SSS, had served as a buffer, thus could also be a critical step for the establishment of CMS genes in natural populations. Our results also suggest that the previously recognized general features of new nuclear gene origination, including (1) recombination of existing genes and/ or previously non-coding sequences, leading to a hybrid gene structure, (2) sequence evolution driven by natural selection, and (3) acquisition of new functions [32,38,39], may also hold true for new mitochondrial gene formation. However, the microevolutionary process of the new mitochondrial genes we demonstrate here are much complicated than that of new nuclear genes reported so far.…”
Section: Discussionmentioning
confidence: 53%
“…So far only a few Drosophila new genes have received evidence for possible functions, such as Jingwei and Sphinx [26,27]. One of the most striking findings in this study is that MDF1, most likely generated de novo from a non-coding sequence, plays very important roles in two fundamental biological processes, namely mating and growth.…”
Section: Mdf1 Is An Unprecedented Example For the De Novo Originationmentioning
confidence: 62%
“…Thus, duplicated genes that have evolved under a model of neofunctionalization provide an interesting case for exploring this question. Although the rise of novel gene functions has been studied in great detail in some examples of duplicated genes (2)(3)(4), how selection and the rise of a new function in the duplicated copy affects the evolution of the sister copy remains unclear. This evolutionary interference has not yet been studied in paralogous genes.…”
mentioning
confidence: 99%